EFFECTIVENESS OF THE GROUP TRIPLE P (POSITIVE PARENTING PROGRAM) IN AN ORPHANAGE CONTEXT IN LAHORE, PAKISTAN - Amina Khalid; Alina Morawska; Karen Turner (International Journal of Child, Youth & Family Studies)
An inadequate caregiving environment in an orphanage can negatively impact children’s well-being, while a lack of specialized training can induce work-related stress and lower self-efficacy among caregivers. This study examined the effectiveness of the Group Triple P (positive parenting program) with caregivers of children in Pakistani orphanages. Fourteen caregivers across three orphanages completed self-report questionnaires and took part in Group Triple P. A repeated measures ANOVA indicated that the personal well-being of the caregivers improved following intervention. There was also a significant increase in caregivers’ parenting efficacy and a decrease in the use of dysfunctional parenting practices. The frequency and number of children’s challenging behaviors was reported to decrease significantly, along with a significant increase in warmth and reduction in negativity in caregiver–child relationships. This study was the first to implement Group Triple P in an orphanage context. The outcomes support the use of an evidence-based parenting intervention with orphanage caregivers who are in a proxy parenting role.